Peningkatan Kemampuan Digital dengan Pelatihan Luring Menggunakan Media Pembelajaran Online - Vigo Dewangga; Enik Rukiati; Nodistya Septian Indrastana; Renata Kenanga Rinda; Yuslaili Ningsih (TAAWUN, 2022)
Corona virus pandemic have shocked all over the world. All human being activities have collapsed because of the covid 19 outbreak. Schools closed, workplaces shut down, and places of worship are closed. The process of teaching and learning should go on eventhough some schools close down. The ministry of education determine to close schools and also ask students study at their home in order to stop corona virus transmission. They are in collaboration with TVRI to convey educational content during certain time. Furthermore, many schools apply for students study at home. They try to link the teachers and the students through online learning platforms. Under these inconvenience conditions, the parents and students have had to rapidly adjust in this situation and condition to make sure that the online learning runs well. The obstacles for parents and students learning from home are they don’t understand how to use various features on the zoom cloud meeting and google classroom. Furthermore, most of parents feel that they are not able to assist their children in online learning from home during corona virus pandemic. This community service focuses on the online learning platform, namely Zoom cloud meeting and Google classroom. The aim of this community service is to develop parents and students’ competence at online learning platform. The community service was conducted in Tegal Besar Estate. The result revealed that parents and students are able to use the zoom cloud meeting and google classroom’s features as an online learning platform during covid-19 outbreak.